Context and Implications Document for: Positive psychology school‐based interventions: a reflection on current success and future directions. Issue 1 (30th August 2016) - Chodkiewicz, Alicia R.; Boyle, Christopher
Abstract : This guide accompanies the following article: Chodkiewicz, A. R. & Boyle, C., Positive psychology school‐based interventions: a reflection on current success and future directions, Review of Education, DOI:10.1002/rev3.3080